Perlindungan Hukum terhadap Pembeli dalam Jual Beli Tanah yang Belum Dibalik Nama - Pandia, Dion; Yetniwati, Yetniwati; Yahya, Taufik (Recital Review, 2025)
Land sale and purchase transactions often end with the issuance of a Sale and Purchase Deed (AJB) without being followed by the transfer of the certificate name. This situation creates legal uncertainty for buyers, even though the payment has been completed and physical possession of the land has been transferred. Such conditions reveal a gap in public understanding as well as in land administration practices, which may potentially lead to disputes. This study aims to analyze the legal consequences of land transactions without a name transfer and the forms of legal protection available to disadvantaged buyers. The research employs a normative juridical method with a statutory approach and analysis of secondary data, including literature, regulations, and relevant court decisions. The findings show that legal certainty can only be guaranteed if the name transfer process is carried out in accordance with the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997 on Land Registration. Nevertheless, even without a certificate transfer, buyers may still obtain preventive legal protection through the AJB and physical control of the land, as well as repressive protection through litigation in court. Therefore, the transfer of certificate ownership constitutes a crucial instrument in ensuring legal protection and certainty of land rights for buyers.